Matematică
katecute
2015-11-16 00:10:24
2x+3/x+2=x-1/x-2 cine mă ajuta
Răspunsuri la întrebare
Zhevon
2015-11-16 05:53:47

(2x+3)/(x+2)=(x-1)/(x-2) (2x+3)(x-2)=(x+2)(x-1) 2x²+3x-4x-6=x²+2x-x-2 2x²-x-6=x²+x-2 x²-2x-4=0 x²-2x-4+5-5=0 x²-2x+1-5=0 (x-1)²-(√5)²=0 (x-1-√5)(x-1-√5)=0 (x-1-√5)=0   x=1+√5 (x-1+√5)=0  x=1-√5 sau x²-2x-4=0 Δ=(-2)²-4×(-4)×1=4+16=20 x₁=[-(-2)+√20]/2=(2+2√5)/2=1+√5 x₂=[-(-2)-√20]/2=(2-2√5)/2=1-√5

nicolaemariana
2015-11-16 05:55:02

Salut, (2x+3)/(x+2) = (x-1)/(x-2) (2x+3)(x-2) = (x-1)(x+2) 2x(x-2)+3(x-2) = x(x+2)-1(x+2) 2x²-4x+3x-6 = x²+2x-x-2 2x²-x-6 = x²+x-2 2x²-x-6-x²-x+2 = 0 x²-2x-4 = 0. ∆ = b²-4ac ∆ = 4+16 ∆ = 20. x1 = (-b-√∆)/2a x1 = (2-2√5)/2 x1 = 2(1-√5)/2 x1 = 1-√5. x2 = (-b+√∆)/2a x2 = (2+2√5)/2 x2 = 2(1+√5)/2 x2 = 1+√5. S = {1-√5 ; 1+√5}. Succes! :3

Adăugați un răspuns